Waiting for manna - Sāhu, Sarojinī (Indian Age Communication, 2008)
Waiting for manna -- Few pages form vacant lot -- Sorrows unending -- Smoke -- Threshold -- Flies -- Wall clock -- Burden of proof -- Beyond reach -- The rape